Investigation of the Impact of Gravity on the Downstream Flow of Fluid in a Bifurcated Channel - Egbo A. Chijioke; Abbey M. Tamunoimi; Eromosele Abumere; Obomanu Tamunotonjo; Olumide M. Oladapo; Odera N. Okechukwu (East Asian Journal of Multidisciplinary Research, 2023)
The study analyzed numerically the data obtained from experiment where water, diesel, crude oil and peanut oil are made to represent various categories of fluid samples with similar physical properties. Each of the fluid sample are allowed to flow through a bifurcated channel of 10o, 20o, 30o, 40o, 50o and 60o angles of bifurcation, an experimental process to be iterated for recovery volumes of 100ml, 200ml, 300ml, 400ml and 500ml. result of the dimensionless Froude number for each of the fluid sample were compare and presented based on their physical properties and based on the dimension of the symmetrical channel they flow through.